Affinity Purification and Immobilization of Chitinase from Bacillus sp.R2. (2015) - Cheba, Ben Amar; Zaghloul, Taha Ibrahim; EL-Mahdy, Ahmad Rafik; EL-Massry, Mohammad Hisham
Abstract: Bacillus sp. R2 chitinase was purified to homogeneity using ammonium sulphate precipitation at 80% saturation, affinity chromatography on swollen crab shell chitin column, and followed by gel filtration chromatography on Sephadex G-100; the enzyme was purified to 14.89-fold and yield of 14.77%, respectively. Furthermore the purified chitinase was subjected to three immobilization techniques on ten various solid carriers;1-physical adsorption immobilization on activated charcoal and silica gel carriers; 2-covalent binding on crab shell chitin and chitosan; 3-Ionic binding on CM-Sepharose, Q-Sepharose, DEAE Cellulose, Amberlite IRC 50, Amberlite CG-120 (NA) and Amberlite CG -4B (OH)respectively. Immobilization results revealed that covalent and ionic binding were the best techniques whereas chitosan, Amberlite IRC50 and chitin gave the highest immobilization yields 72.9, 70.26 and 63.53% with the highest activity yields 63.36, 58.26 and 53.03% respectively. These findings improve the effectiveness of swollen crab shell chitin as matrix for chitinase affinity purification whereas chitin and chitosan as active natural biopolymers for chitinase continuous production through immobilization.